THE EFFECT OF COMPANY CHARACTERISTICS AND AUDIT FIRM ON GOING CONCERN AUDIT OPINION ISSUED BY AUDIT FIRM - Hana, Hana; Triani, Ni Nyoman Alit (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study was conducted with the aim of determining the effect of company characteristics and audit firm on going concern audit opinion in companies in all sectors listed on the IDX in 2021-2022. This research was conducted using quantitative methods with the dependent variable going concern opinion and independent variables, namely audit firm size, audit fees, liquidity, solvency, leverage, company size, and company growth as well as two control variables, namely losses and bankruptcy probability. The data was tested using binary logistic regression, the results obtained from this study are that the audit firm size variable has a negative effect on going concern opinion, audit fees have no effect on going concern opinion, liquidity has a positive effect on going concern opinion, solvency has no effect on going concern opinion, leverage has no effect on going concern opinion, company size has no effect on going concern opinion, company growth has no effect on going concern audit opinion, losses have a positive effect on going concern audit opinion and probability affects going concern opinion.